STRATEGI MANAJEMEN SEKOLAH DALAM PENGEMBANGAN INFORMASI DAPODIK DI INTERNET - Annida Annida; Syahrani Syahrani (EDUCATIONAL JOURNAL : General and Specific Research, 2022)
Through an integrated dapodik management information system strategy (integrated) can provide more accurate and quality information to support the development of operations, management, and decision-making functions within an organization. The school's strategy in analyzing the internal and external environment, the chosen strategy in improving the quality of basic education is through a curriculum program strategy, a program to improve the quality of educators and education staff. Therefore, we need a qualified operator and educator who can create conditions so that all components are interrelated and can work well together to achieve school goals.